Trends of Economicand Political Cooperation Between Canadaand Countries of the European Union - P. U. Baryshnikov (Мир новой экономики, 2018)
In recent decades, the world faces active integration processes at both regional and global levels. Trade and economic unions are created and agreements are signed. One of the latest agreements signed at the interregional level is the Comprehensive Economic and Trade Agreement (CETA) - an agreement that covers foreign economic cooperation between Canada and the European Union (EU). CETA is an example of a new model of multilateral, comprehensive regulation of trade and economic relations. CETA went beyond the WTO, covering new areas of foreign economic cooperation. This article examines the history of international economic cooperation between Canada and the EU, analyzes the development of foreign economic relations between countries. In particular the article considers the background for CETA signing as the culmination of economic interaction between Canada and the EU countries. The author analyzes the agreement and identifies the priority areas of current and future potential cooperation. This study is one of the first in the field of studying interregional integration of a new type. The study of this issue can be useful for integration in other interregional agreements.